Modelling of solid oxide cell oxygen electrodes. (1st April 2023) - Panisset, Silvère; Burriel, Mónica; Laurencin, Jérôme; Jauffres, David
Abstract: Numerical models are versatile tools to study and predict efficiently the performance of solid oxide cells (SOCs) according to their microstructure and composition. As the main contribution to the cell polarisation is due to the oxygen electrode, a large part of the proposed models has been focused on this electrode. Electrode modelling aims to improve the SOCs performance by serving as a guide for the microstructural optimisation, and helps to better understand the electrochemical reaction mechanisms. For studying the electrode microstructure, three categories of models can be distinguished: homogenised models, simplified geometry based models, and reconstructed microstructure based models. Most models are based on continuum physics, while elementary kinetic models have been developed more recently. This article presents a review of the existing SOCs models for the oxygen electrode. As a perspective, the current challenges of electrode modelling are discussed in views of a better prediction of the performance and durability, and more specifically for the case of thin-film SOCs.